First record of a Late Holocene fauna associated with an ephemeral fluvial sequence in La Pampa Province, Argentina - Montalvo, Claudia (2017)
The ﬁrst Late Holocene mammal assemblage (mainly micromammals) of La Pampa Province was found in Quehue paleontological site, associated with an ephemeral ﬂuvial sequence. Taphonomical features of the collected materials were evaluated in order to increase the knowledge of the ancient vertebrate communities of this area and to interpret the origin of the assemblages. Field data and taphonomic analysis of the specimens, suggested the recognition of three assemblages with different taphonomic histories: 1) large to medium sized mammals; 2) micromammals found inside burrows or associated with them; and 3) discrete accumulations of micromammals and other microvertebrates (amphibians, reptiles and birds). Additionally, the paleoenvironmental analysis based mainly on the record of small mammals reﬂected the predominance of semi-arid conditions associated with a mosaic of open shrub steppe, grasslands and xerophytic forests of Espinal, similar to the present one in the Quehué Valley area. However, the presence of Lestodelphys halli in the Quehué site during the Late Holocene (~1.2 ky BP), suggests a more heterogeneous environment and perhaps relative colder and drier than current times, which are featured by more mesic conditions and anthropic activities, mainly agriculture and livestock during the last centuries.